Transcatheter Arterial Chemoembolization and Chemotherapy plus Sorafenib in a Large Hepatocellular Carcinoma with Arterioportal Shunt - Jun Chen; Shixi Chen; Wei Xi; Bei Wu; Hui Yu; Yang Gao (Case Reports in Oncological Medicine)
Introduction. Arterioportal shunts (APS) are sometimes encountered in patients with hepatocellular carcinoma (HCC) and associated with poor prognosis. The management of HCC with APS is a challenge so far. Case Presentations. We report here in detail a 37-year-old man who was diagnosed as an advanced HCC accompanied with severe APS and treated by two sessions of transcatheter arterial chemoembolization (TACE) and three sessions of transcatheter arterial chemotherapy (TAC) plus sorafenib therapy. The tumor shrinks were revealed continuously during 152 days after the diagnosis. Although tumor progress emerged at 209 days after the diagnosis, the patient remarkably achieved 366-day survival. Discussion. TACE plus sorafenib may be a promising treatment for advanced HCC accompanied with APS. Prospective case-control studies should be advocated to evaluate the combination of TACE, TAC, and sorafenib in the management of HCC with APS.